Occupational Health and Safety Management System (SMK3) at the workshop of vocational high schools - Adilla Desy Rizbudiani; Amat Jaedun (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2021)
This research aims to identify the planning implementation, idenfety Management System (SMK3) at the workshop of vocational high schools in the major of construction and property engineeringtify the implementation, and identify the evaluation of the implementation of the Occupational Health And Safety Management System (SMK3) at the workshop of Construction and Property Engineering Study Program, one of the Vocational High Schools in Central Java. This research is qualitative by using data collection techniques in interviews, observations, and documentation the validity of the data using source triangulation. Data analysis used descriptive qualitative. The results show that the workshop building at one of the Vocational High Schools in Central Java has been well planned in its implementation of OHS. The implementation of OHS is categorized as quite well implemented. The evaluation of the implementation of OHS is categorized as quite well done. Hence, the Occupational Health and Safety (OHS) management system at the Vocational High Schools needs to be improved. The school can collaborate with stakeholders to follow up on the management system of OHS.